Lip vitiligo: a clinico-epidemiological study in a tertiary hospital of South India - A. S Savitha; Shashi Kumar BM; Raghunatha Reddy R; Sana Mariam Sankey (Wolters Kluwer Medknow Publications, 2023)
Vitiligo is a common autoimmune pigmentary disorder characterized by destruction of functional melanocytes resulting in the appearance of depigmented patches on the skin and mucosa. These lesions pose a cosmetic challenge. The involvement of the mucosa is less, but may be the first symptom of this pathology. Depigmentation in the lips can be more easily observed and patients can be counseled regarding the condition and guided for treatment. Aims: The study describes the various clinic-epidemiological factors associated with lip vitiligo. Materials and Methods: The study sample included 100 patients of lip vitiligo of all age groups and gender. Patients with a history of herpes labialis, and history suggestive of post inflammatory depigmentation of lips secondary to various causes were excluded from this study. Also, patient vitiligo patients without lip involvement were excluded. The frequency, site, extension, association with vitiligo elsewhere, and systemic association were noted and tabulated. Results: Among 100 patients, 57 were males and 43 were females. Majority of our study subjects (63%) had onset of vitiligo between 11 and 30 years and 24% between 31 and 50 years. In the present study, 41 patients had only lip vitiligo, 55 patients had lip and vitiligo in other parts, four had involvement of lip and genital mucosa. Out of 100 patients, 71 complained that the lips were the initial lesion. The most type of vitiligo seen in our study subjects was the isolated lip vitiligo (41) and the least common was universal vitiligo (2). Leukotrichia was seen in three patients. In our study six patients had exclusive upper lip vitiligo and 40 patients had lower lip vitiligo. The remaining patients had both lower lip and upper lip involvement. Angle of the mouth was involved in 31 patients and five had marginal extension onto the skin. Of 100 patients with vitiligo nearly 19% had atleast one co-morbid condition. The most common autoimmune disease was thyroid dysfunction seen in 17% of patients. Conclusion: Though rare, lip vitiligo could be one of the earliest presentations of vitiligo and will aid in counseling the patients regarding the chronicity and thereby reduce the psychological morbidity. The data on lip vitiligo is sparse and to the best of our knowledge, there is no study on the demographic characteristics and clinical patterns of lip vitiligo.